The impact of the implementation of Municipality Ordinance No. 2008-752 otherwise known as "An ordinance prohibiting the use of plastic bags on dry goods and regulating its utilization on wet goods and prohibiting the use of Styrofoam in the Municipality of Los Banos and the prescribing penalties thereof" - Magat, Mira Lian J; Agra, Krizzia L. (Manila: National University, 2010)
The importance of this research is to warn people specifically those establishment producing plastic wasters and those businesses that are using plastics that they are contributing to the further damage of Los Banos. Through this, they will realize and understand the problems and form some ideas on how to lessen the use of plastics without affecting their ventures like helping out in recycling at EWPC, abiding by the schedule of waste disposal among others. It also aims to introduce the concept to those who will be venturing into the business and to the students who have little exposure to this kind of problem.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- Chapter 1. The Problem and its Background -- Chapter 2. Review of Related Literature -- Chapter 3. Research methodology -- Chapter 4. Presentation, Analysis, and Interpretation of data -- Chapter 5. Summary of Findings, Conclusions, and Recommendations -- Bibliography -- Appendices
Research Method : Descriptive Research Design
Includes bibliographical references.